1992
DOI: 10.1111/j.1365-2621.1992.tb01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Dough mixing and breadmaking properties of quinoa‐wheat flour blends

Abstract: Flour blends of quinoa-wheat containing 0, 5, 10, 15, and 20% of manually dehulled quinoa meal or flour were evaluated for dough mixing and breadmaking properties and liking of the bread by a small panel. Increasing amounts of quinoa meal or flour increased farinograph absorption and dislike of bread for most of the panel. Dough development time increased with increase in meal but decreased with increase in quinoa flour. At 10% inclusion levels differences in liking from control 100% wheat flour bread were sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 2 publications
4
38
0
2
Order By: Relevance
“…The results for bread with quinoa flour agree with previous reports (Lorenz and Coulter, 1991;Chauhan et al, 1992;Morita et al, 2001;Rosell et al, 2009). Loaf volume of breads decreased with quinoa replacement levels up to 10%.…”
Section: Bread Quality Parameterssupporting
confidence: 83%
See 1 more Smart Citation
“…The results for bread with quinoa flour agree with previous reports (Lorenz and Coulter, 1991;Chauhan et al, 1992;Morita et al, 2001;Rosell et al, 2009). Loaf volume of breads decreased with quinoa replacement levels up to 10%.…”
Section: Bread Quality Parameterssupporting
confidence: 83%
“…The amino acid balance of quinoa is better than that of wheat or corn because the first limiting amino acid, lysine, is present in relatively higher amounts in quinoa seeds (Lorenz and Coulter, 1991). Different studies focused on breadmaking with quinoa-wheat composite flour have reported excellent results with substitutions lower than 10% (Lorenz and Coulter, 1991;Chauhan et al, 1992;Morita et al, 2001;Rosell et al, 2009) On the other hand, potatoes (Solanum tuberosum L.) are fourth among the food crops in the world after wheat, rice and corn in total production. They contain good quality edible grade protein, dietary fiber, several minerals and trace elements, essential vitamins and little or negligible fat (Misra and Kulshrestha, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Reduction in bread volume and quality as a result of blending wheat flour with more than 5% oil seeds or legume flour and protein concentrates have been reported by various workers [26,27]. An increase in loaf weight from 364.3g (sample A) to 558.4g (sample G) was observed.…”
Section: Physical Properties Of the Breadmentioning
confidence: 65%
“…The five blends of composite flour were baked into bread using the straight dough method [18]. The wheat flour and composite flours were mixed with 5 g salt, 40 g shortening, 20 g yeast and 60g sugar in 500 ml water followed by stirring using a Kenwood mixer (Model A 907 D) for 5 min to obtain a dough.…”
Section: Baking Processmentioning
confidence: 99%
“…Initial and final volumes at the beginning and end of fermentation and proofing were determined. Fermentation and proofing rates were calculated by dividing the average volume increase due to fermentation and proofing by the time taken for fermentation and proofing respectively [18]. Bread characteristics were evaluated by measuring the loaf weight, loaf volume and specific loaf volume.…”
Section: Determination Of Physical Properties Of Dough Andmentioning
confidence: 99%